(untitled) (Research, Society and Development, 2023)
The species of Digitalis lanata and Digitalis mariana are exploited industrially for the production of digoxin and digitoxin, cardenolides used clinically in congestive heart failure. Environmental factors, mainly biotic factors, interfere with plant production. Problems in the conventional production of Digitalis mariana by seeds have affected the production of cardenolides by the plant. Plant tissue culture is based on the totipotentiality of cells and applies various forms of in vitro culture. This technique has been used to create genetic variability and also large-scale micropropagation of plants for the commercial market. In plants, selenium (Se) at low concentrations is beneficial for metabolism and stimulates growth. In addition, there are reports that Se can help plants to remain physiologically active for longer, increasing plant production. Thus, the objective was to evaluate the influence of the application of selenium sources on the growth, total cardenolides and photosynthetic pigments of Digitalis mariana subsp. heywoodii cultivated in vitro. Two sources of selenium were tested: sodium selenate and sodium selenite at concentrations of 0, 1, 10, 20, 50, 100 mg L-1. After 40 days, growth, production of photosynthetic pigments and cardenolides were evaluated. The most suitable source for the species is selenate, as well as the best concentration is 1mg L-1, which promoted growth in most of the evaluated variables, in addition to increasing the production of chlorophyll a, chlorophyll b, carotenoids and cardenolides. The use of selenium in the D. mariana subsp. heywoodii can be an alternative to optimize the cultivation of the species in vitro.